Co‐Deposition of Plasma‐Polymerized Polyacrylic Acid and Silver Nanoparticles for the Production of Nanocomposite Coatings Using a Non‐Equilibrium Atmospheric Pressure Plasma Jet. Issue 6 (26th October 2015) - Liguori, Anna; Traldi, Enrico; Toccaceli, Elena; Laurita, Romolo; Pollicino, Antonino; Focarete, Maria Letizia; Colombo, Vittorio; Gherardi, Matteo
Abstract : A single step process for the deposition of nanocomposite coatings with silver nanoparticles (AgNPs) embedded in a plasma‐polymerized polyacrylic acid (pPAA) matrix and performed using a non‐equilibrium atmospheric pressure plasma jet is presented. Acrylic acid (AA) and AgNPs dispersed in ethanol (EtOH) are used as precursors and are separately injected in the plasma region directly; Ar is used as plasma gas and also as carrier gas for both precursors. Scanning electron microscopy (SEM) and ATR‐FTIR analysis show the deposition of a micrometric pPAA coating on the polyethylene (PE) film used as substrate; AgNPs embedded in the polymeric matrix are visible in SEM pictures and their presence is confirmed by XPS and EDS analysis. X‐ray photoelectron spectroscopy (XPS) also highlights a high retention of carboxylic groups in the pPAA chemical structure and the surface oxidation of AgNPs. Preliminary results of the antibacterial activity of the co‐deposited coatings are presented. Abstract : The co‐deposition of plasma‐polymerized polyacrylic acid and silver nanoparticles for the production of nanocomposite coatings by means of a non‐equilibrium atmospheric pressure plasma jet is reported. The characterization of the chemical structure and the morphology of the nanocomposite coatings, jointly to the qualitative investigation of their antimicrobial properties, is presented.